Handbook of vinyl polymers : radical polymerization, process, and technology - Mishra, Munmaya K.; Yagci, Yusuf, 1952-; Mishra, Munmaya K. (Taylor & Francis, 2008)
Radical polymerization is one of the most widely used means of producing vinyl polymers, supporting a myriad of commercial uses. Maintaining the quality of the critically acclaimed first edition, the Handbook of Vinyl Polymers: Radical Polymerization, Process, and Technology, Second Edition provides a fully updated, single-volume source on the chemistry, technology, and applications of vinyl polymers. Emphasizes radical initiating systems and mechanisms of action ... Written by renowned researchers in the field, this handbook is primarily concerned with the physical and organic chemistry of radi.- Resumé vydavatel
Keywords: polymery; polymerizace; polymers; polymerization; vinylové polymery; elektronické knihy; sborníky; electronic books; papers of several authors